Elucidating biotransformation pathways of ofloxacin in lettuce (Lactuca sativa L). (May 2020) - Tadić, Đorđe; Gramblicka, Michal; Mistrik, Robert; Flores, Cintia; Piña, Benjamin; Bayona, Josep Maria
Abstract: Antibiotics can be uptaken by plants from soil desorption or directly from irrigation water, but their metabolization pathways in plants are largely unknown. In this paper, an analytical workflow based on high-resolution mass spectrometry was applied for the systematic identification of biotransformation products of ofloxacin in lettuce. The targeted metabolites were selected by comparing the mass chromatograms of exposed with control samples using an advanced spectra-processing method (Fragment Ion Search). The innovative methodology presented allowed us to identify a total of 11 metabolites, including 5 ofloxacin metabolites that are being reported for the first time in plants. Accordingly, major transformation pathways were proposed revealing insight into how ofloxacin and related chemicals are metabolized in lettuce. Furthermore, the influence of biotransformation on potential residual antimicrobial activity of identified compounds was discussed. Human exposure to antibiotics at doses below the minimum inhibitory concentrations is crucial in human risk assessment, including food ingestion; however, in the case of ofloxacin presented results reveal that plant metabolites should also be considered so as not to underestimate their risk. Graphical abstract: Image 1 Highlights: High-resolution mass spectrometry was applied for the identification of metabolites of ofloxacin in lettuce. A total of 11 biotransformation products were identified with different confidence levels. Major transformation pathways responsible for the detoxification and metabolization of ofloxacin were proposed.